49.6k views
2 votes
Enter the values for the highlighted variables that show how to subtract the rational expressions correctly:

User Mr Matrix
by
5.8k points

2 Answers

6 votes

Answer:

a = 6

x^2 + 6x is equal to x(x+6)

b=2

Denominator and numerator of the first term are multiplied by x.

c=6

Second term is multiplied by (x-6)/(x-6)

d=2

Now that they have the same denominator, the two terms are combined. 2 is the coefficient of the first term

e=6

In the same way as d is carried over from b, e is carried over from c.

f = 6

2x - x + 6 = x + 6

g = 1

We factor out the (x+6) from the numerator and denominator.

User Ivorykoder
by
5.7k points
6 votes

Answer:

a= 6

b= 2

c= 6

d= 2

e= 6

f= 6

g= 1

Explanation:

i like math

User Kabaros
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.